1997
DOI: 10.1016/s0896-6273(00)80357-8
|View full text |Cite
|
Sign up to set email alerts
|

Gated Access to the Pore of a Voltage-Dependent K+ Channel

Abstract: Voltage-activated K+ channels are integral membrane proteins that open or close a K(+)-selective pore in response to changes in transmembrane voltage. Although the S4 region of these channels has been implicated as the voltage sensor, little is known about how opening and closing of the pore is accomplished. We explored the gating process by introducing cysteines at various positions thought to lie in or near the pore of the Shaker K+ channel, and by testing their ability to be chemically modified. We found a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

41
471
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 471 publications
(517 citation statements)
references
References 44 publications
41
471
4
Order By: Relevance
“…For example, studies using intracellularly applied molecules that block the permeation pathway of CNG channels, such as divalent ions (18), tetracaine (19,20), or quaternary ammonium ions (21), have shown that blockade is not state-dependent, as if these molecules can access the pore in both open and closed channels, which is in stark contrast with the blockade properties observed in K V channels (10,11,14,(22)(23)(24). In addition, experiments examining the state dependence of cysteine modification by intracellular application of methanethiosulfonate (MTS) reagents have failed to show dramatic differences between open and closed states in the inner-vestibule region (21,25,26), results that are inconsistent with an intracellular gate in TM6, as shown in K V channels (12,15).Several studies indicate that the pore region of CNG channels plays a role in gating. For example, accessibility of cysteine reagents applied from the intracellular (27, 28) and the extracellular (27-29) side of the channel to cysteines substituted along the entire P region have shown that modification of some residues in this region perturbed normal gating by cGMP.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For example, studies using intracellularly applied molecules that block the permeation pathway of CNG channels, such as divalent ions (18), tetracaine (19,20), or quaternary ammonium ions (21), have shown that blockade is not state-dependent, as if these molecules can access the pore in both open and closed channels, which is in stark contrast with the blockade properties observed in K V channels (10,11,14,(22)(23)(24). In addition, experiments examining the state dependence of cysteine modification by intracellular application of methanethiosulfonate (MTS) reagents have failed to show dramatic differences between open and closed states in the inner-vestibule region (21,25,26), results that are inconsistent with an intracellular gate in TM6, as shown in K V channels (12,15).Several studies indicate that the pore region of CNG channels plays a role in gating. For example, accessibility of cysteine reagents applied from the intracellular (27, 28) and the extracellular (27-29) side of the channel to cysteines substituted along the entire P region have shown that modification of some residues in this region perturbed normal gating by cGMP.…”
mentioning
confidence: 95%
“…A large body of evidence, using a variety of approaches, has established that K V channels open and close their permeation pathway at the intracellular end of the pore (10)(11)(12)(13)(14)(15)(16)(17). Attempts to extend those ideas to CNG channels have encountered some resistance.…”
mentioning
confidence: 99%
“…Genetic analysis, coupled with biophysical analysis, of TOK1 has assisted in the identification of what we call the PP region, the cytoplasmic end of the P-region-following membrane domain, which has been found to be intimately involved with gating of cation channels (1,2,3). Our analyses have also pointed to the existence of functional domains that, on first glance, appeared unique to TOK1, including a filter-specific gating ( Fig.…”
mentioning
confidence: 75%
“…Mutations exclusively in the ''PP'' region (the end of M6 and M8 in the case of TOK1) specifically disrupt the C states (1) suggesting that they result from a constriction of the inner mouth of the pore, akin to deactivation-type gating in other cation channels (2,3,23,24). We have proposed that the K ext ϩ ͞Vm dependence of C could simply result from the open noncollapsed filter preventing inner pore gating transitions (4).…”
mentioning
confidence: 99%
“…Notably, the study on KvLm channels revealed that pore only module can populate at open state, suggesting that the pore of Kv channels may also reside in between closed-activated and open state [16]. The gating of the Kv channel pore involves both the lower bundle-crossing gate at the cytoplasmic entrance to the channel and the upper gate at the selectivity filter close to the outer mouth of the channel [54,55]. By contrast, the gating of K2P channels was thought to occur through their upper gate [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%